Focusing on explicit debriefing for novice learners in healthcare simulations: A randomized prospective study. (February 2021) - Secheresse, Thierry; Lima, Laurent; Pansu, Pascal
Abstract: Introduction: Debriefing is essential in simulation-based training, but it is not clear what exactly constitutes a successful debriefing session. Research in educational sciences shows that a structured, explicit and trainer-directed approach is systematically more effective than an implicit, reflective approach with minimal guidance, particularly for novice or intermediate learners. The aim of this study is to compare explicit strongly trainer-guided debriefing with implicit and weakly guided debriefing in nursing training. Method: Single-centre randomized prospective study comparing effectiveness of explicit and implicit debriefing techniques. We focused on the description and the analysis phases of the debriefing. Our main aim was to assess the effectiveness of debriefing in terms of knowledge improvement. We also assessed its effectiveness for self-efficacy and self-confidence. Results: 136 nursing students participated in 46 simulation sessions. Knowledge, self-efficacy and self-confidence increased in all conditions. The results also showed that debriefing with explicit analysis improved learning significantly when compared to the control session. Conclusion: Although the results revealed a beneficial effect of simulation training on self-efficacy, the explicit debriefing technique was shown to produce greater knowledge improvement than the implicit debriefing method in novice learners. Consequently, debriefing technique should be adapted to the objectives of the training and learners. Highlights: Explicit debriefing is more effective than implicit debriefing for novice learners. Explicit debriefing involves active trainer management of the debriefing. Presenting new information is an explicit manner is more effective for novice learners.